Parental risk factors for fever in their children 7–10 days after the first dose of measles-containing vaccines. Issue 4 (2nd April 2020) - Zerbo, Ousseny; Modaressi, Sharareh; Goddard, Kristin; Lewis, Edwin; Bok, Karin; Gans, Hayley; Klein, Nicola P.
ABSTRACT: We evaluated whether parental clinical conditions were associated with fever after a first dose of measles-containing vaccine (MCV) in the child in a cohort study including 244, 125 children born in Kaiser Permanente Northern California between 2009 and 2016 who received MCV between ages 1 and 2 years. Each child was linked with his/her mother and father when possible. Parental clinical conditions present before and after their child's birth were identified. We defined fever in the children as clinic and emergency department visits with a fever code 7–10 days after a first dose of MCV ("MCV-associated fever"). We evaluated parental clinical conditions associated with MCV-associated fever using multivariate logistic regression analyses. After adjusting for multiple factors, including healthcare utilization, maternal fever [odds ratio (OR) = 1.19, 95% confidence interval (CI) 1.06–1.32], fever after MCV (OR = 5.90, 95% CI 1.35–25.78), respiratory infections (OR = 1.20, 95% CI 1.10–1.31), migraine (OR = 1.14, 95% CI 1.05–1.24), syncope (OR 1.14, 95% CI 1.01–1.27), and essential thrombocythemia (OR = 1.93, 95% CI 1.15–3.25) were significantly associated with MCV-associated fever. Paternal respiratory infections (OR = 1.15, 95% CI 1.05–1.27), fever associated with respiratory infections (OR = 1.47, 95% CI 1.23–1.76), and vitiligo (OR = 1.63, 95% CI 1.06–2.53) were significantly associated with MCV-associated fever. Parental clinical conditions, specifically fever alone and fever associated with respiratory infection, are associated with fever in their child 7–10 days after MCV.